Physical activity and subjective well-being in elderly - Silva, Adriana (2019)
Physical activity, although recognized as fundamental in the prevention of non-communicable diseases and in the improvement of subjective well-being, show low levels among the Portuguese elderly. This ex-post-facto study was developed to characterize the levels of physical activity and subjective wellbeing among the elderly, as well as the possible relations between both and the socio-demographic and health variables consequences in this sense. Of the convenience sample of 100 participants, aged between 65-89, 66 were women. 69 lived inland (mostly away from cities) while 31 lived in coastal areas. 56 lived in rural areas and 44 lived in cities. 54 were married while 69 did not live alone. The instruments used in data collection were the Modified Baecke Questionnaire (Physical Activity) (2014), Satisfaction with Life Scale and Positive and Negative Affect Schedule (Subjective Well-Being) (1991, 1992). Descriptive and inferential analysis were performed using SPSS-24 with p<.05 as the cut off point for significance. The elderly with higher median scores in Baecke had better results (p <.05) in subjective well-being. There was no significant difference among those who lived alone and those who were married as well as those living in the coastal region but a negative affect was found in women and the urban population. Our findings showed that the perception of health was positively correlated with physical activity and subjective well-being among the sample. The practice of physical activity is a key element of subjective well-being, because it mitigates negative affectivity and has a more positive impact than any socio-demographic or health variable.